IMPLEMENTING COLLABORATIVE STRATEGY TO IMROVE READING COMPREHENSION THE ELEVENTH GRADERS OF SMK KERTHA WISATA MALANG - Chindy Hanggara Rosa Indah; Yahmun (UIBU, 2019)
In this classroom action research, the researcher used the model of classroom action research developed by Kemmis and Mc Taggart (1999). There are four steps of teaching. Before doing those four steps, the researcher did reconnaissance step by observing the class situation and interviewing the class teacher and the students to know the problems. After knowing the problems, the researcher started to do the four steps of teaching they were planning, implementing, observing, and reflecting. The findings of this result showed that teaching reading comprehension using collaborative strategic reading improved the students` reading comprehension skill. In the first cycle the result was not satisfactory. The students were still passive in class because they did not understand about the method and many of them still found difficulty in understanding the texts. Their mean score of the first cycle was under the MMC. The criterion of success is when students give good response to this method, and also get the mean score that reach the MMC. After implementing the second cycle, the researcher found that the students were more enthusiastic because they knew about the topics of the texts and enjoyed comprehending the texts using CSR. They felt that the method was not boring. Besides that, the students` mean score was 72.85. The second cycle succeeded and proved that the students` mean score improved. It was above the MMC.